Factors associated with greater potential for alcohol misuse among the students of the Gorenjska region - Sanela Pivač; Brigita Skela-Savič (Nurses and Midwives Association of Slovenia, 2016)
Introduction: Excessive alcohol consumption can stem from different biological, social, environmental, or psychological factors (e.g. peer influence, desire to be accepted within a social group, family history with alcohol addiction, availability of alcohol beverages, poor academic performance, low self-image, etc.). The aim of study was to determine the risk factors associated with alcohol consumption among the undergraduate students in the Gorenjska region. Methods: A quantitative non-experimental method of research was employed. The data were collected through a structured questionnaire. The purposive sample consisted of 328 first-year undergraduate students in the Gorenjska region. The research was conducted in May, October and November 2012. The data obtained were analysed using the descriptive statistics and multiple linear regression analysis. Results: The greatest influence on drinking frequency for better sociability and relaxation has the average educational attainment in the last year of secondary education (β = 0.168, p = 0.002). The following factors were identified to have a statistically significant impact on the frequency of alcohol consumption during leisure time: friendship (β = 0.131, p = 0.029), frequent socializing with friends (β = 0.127, p = 0.035), support of the family when in distress (β = - 0. 183, p = 0.001) and the average academic achievement in the last year of secondary education (β = 0.098, p = 0.043). Discussion and conclusion: The risk factors associated with alcohol consumption among the students in the Gorenjska region are mainly social (lack of family support, peer pressure) and personal (low self-image, poor academic achievement and leisure time). Characteristics of the study participants in relation to alcohol consumption do not differ from the rest of the younger population.